Fluid Balance, Interferon-Gamma, Interleukin- 12 and Tumor Necrosis as predictive factors of Survival in Severe Sepsis - Subagyo, Djoko Trihadi Lukmono (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2012)
Background: The cardiovascular derangements of severe sepsis in human include arteriolar, venular dilation, capillary leak, and immunomodulatory response. Intravascular volume replacement during resuscitation most frequently converts the circulation to a high-out put hypotensive state. We hypothesized that patients with severe sepsis had any predicting factors to survive than those who do not.Design and Method: Randomized Clinical Trials were conducted of 110 patients suffered from severe sepsis in ICU/HCU. Admission APACHE II, SOFA scores, IFN- , IL-12, TNF-á, and fluid balance were computed from the extracted data. Patients allowed to severe sepsis treatment according with the International Consensus Committee. Summary estimates using both the Mantel-Haenszel test and precision based approaches were computed for statistical analysis.Result: Of 110 patients ranged in age from 46 to 71 years with a mean (± SE) age of 63.45 ± 3.97 years. The mean admission APACHE II score was 25.96 ± 3.65; and the day 1 SOFA score was 9.57 ± 1.24. Twenty one patients did not survive, Non-survival had higher mean APACHE II than survivals (29.85 vs 20.46), respectively (p < 0.01). Higher first day IFN- , IL-12, TNF-á, and SOFA scores (p< 0.01). Whereas 26 patients who achieved a negative fluid balance of > 500 mL on > of the first 3 days of treatment survived (RR 5.0; 95% CI : 2.3 to 10.7, p < 0.0001).Conclusion: These results suggest that at least 1 day of negative fluid balance (<-500mL), IFN- , IL-12, and TNF-á may be a good independent predictors of survival in patients with severe sepsis. These findings suggest the hypothesis that four independent predictors of severe sepsis portend a good prognosis for a larger prospective study (Sains Medika, 4(1):13-22).